Sleep, internalizing symptoms, and health-related quality of life in children with neurodevelopmental disorders: a cross-sectional analysis of cohort data from three research programs in Canada - McPhee, Patrick G.; Georgiades, Stelios; Andrade, Andrea; Corkum, Penny V.; Vaccarino, Anthony L.; Cheema, Heena; Chepesiuk, Rachel; Iaboni, Alana; Gorter, Jan Willem; , The OBI Cross-integrated Discovery Program Sleep Team (Frontiers in Sleep, 2023)
Objective The objectives of this study were to determine rates of sleep disturbances in children with neurodevelopmental disorders (NDDs) within and across disorders and compared to typically developing (TD) children and to describe differences above and below the clinical cut-off for sleep disturbances. In addition, we explored the associations between demographic variables, severity of disorder, sleep disturbances, internalizing symptoms, and health-related quality of life (HRQOL) in children with NDDs. Method We conducted cross-sectional data analyses of an existing database with community-dwelling children with NDDs (n = 1438) and TD children (n = 140) aged 4–12 years. Parent-reported measures on sleep disturbances using the Children's Sleep Habits Questionnaire (CSHQ), internalizing symptoms using the Revised Children's Anxiety and Depression Scale, and HRQOL using the KINDL-R were assessed. Hierarchical linear regression examined the associations between demographic variables, severity of disorder, sleep disturbances, internalizing symptoms, and HRQOL in children with NDDs. Results Children with NDDs (8.5 ± 2.1 years, 69.9% M) had significantly greater total sleep disturbance index (TSDI) than TD children [(8.6 ± 2.3 years, 60.0% M) (mean difference = 6.88 [95% CI 5.37, 8.40]; p < 0.001) (n = 838 NDDs (58.3%); n = 120 TD (86.7%)]. Children with severe NDDs reported significantly greater TSDI above the clinical cut-off (i.e., ≥41; CSHQ) than those with less severe NDDs (p < 0.001). Internalizing symptoms (β = −0.082 [95% CI −0.144, −0.019]; p = 0.011) and TSDI (β = −0.226 [95% CI −0.380, −0.073]; p = 0.004) were significantly associated with HRQOL in children with NDDs. Conclusion Surveillance and management of sleep and internalizing symptoms are needed to improve HRQOL in children with NDDs. Commonalities in sleep disturbances for children with NDDs support transdiagnostic interventions to treat sleep.